THE GENUS COELOSTEGIA*) Benth. (Bombac.) - REKSODIHARDJO, W. SOEGENG (REINWARDTIA, 1960)
1. The genus Coelostegia is confined to Western Malaysia: Malay Peninsula, Sumatra and Borneo.2. Five species (three of which, C. chartacea, C. kostermansii and C. neesiocarpa are new to science) are described.3. A key to the species is presented.